A MATHEMATICAL MODEL WITH INVENTORY- AND SELLING PRICE-DEPENDENT DEMANDS CONSIDERING ALL-UNITS DISCOUNT AND CARBON EMISSION - Pramesti, Ni Putu Dittarani; Limansyah, Taufik; Lesmono, Dharma (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Customer satisfaction is a crucial aspect that consistently takes center stage in business operations. In light of this, companies must devise appropriate strategies to fulfill customer demands. Consequently, this study delves into examining various factors that facilitate the supply process, including the application of discounts. Moreover, in line with the advancements in eco-green concepts, businesses have begun considering carbon emission factors concerning storage and distribution, which is further supported by the United Nations Framework Convention on Climate Change (UNFCCC). In this context, the paper presents an enhanced version of the economic order quantity model encompassing all-unit discount and carbon emission factors. The developed model entail inventory management approaches where demand relies on inventory levels, inventory levels coupled with selling prices, time-dependent demand, and exponentially declining demand patterns. The primary objective is to aid companies in optimizing their inventory management by determining the optimal quantity of goods while minimizing overall costs. Sensitivity analysis conducted to observe the influence on the reorder point (T), total inventory cost (TC), and total carbon emission (TE) reveals that lower unit purchase prices, driven by high demand, correspond to larger order quantities. Furthermore, it is worth noting that the higher average carbon emission within warehouses result in increased carbon emissions overall.